Involvement of portosystemic shunts in impaired improvement of liver function after direct‐acting antiviral therapies in cirrhotic patients with hepatitis C virus. Issue 4 (13th January 2020) - Tsuji, Shohei; Uchida, Yoshihito; Uemura, Hayato; Kouyama, Jun‐Ichi; Naiki, Kayoko; Nakao, Masamitsu; Motoya, Daisuke; Sugawara, Kayoko; Nakayama, Nobuaki; Imai, Yukinori; Tomiya, Tomoaki; Mochida, Satoshi
Abstract : Aim: Factors responsible for impaired improvement of liver function despite sustained viral response after direct‐acting antiviral agents therapies in cirrhotic patients with hepatitis C virus need to be elucidated. Methods: Liver function and the extent of portosystemic shunting were evaluated for 79 patients with compensated cirrhosis, in whom sustained viral response had been achieved after direct‐acting antiviral agents therapies for hepatitis C virus at least 3 years earlier. Results: Portosystemic shunts were observed in 63 patients (80%). Improvement and worsening, as compared with the baseline, of esophageal/gastric varices after direct‐acting antiviral agents therapies was seen in three patients (4%) and 10 patients (13%), respectively. Portal hypertension‐related events, such as varices and ascites requiring treatment, were observed in six patients (8%), in whom three patients showing worsening of Child–Pugh scores were included. Multivariate analysis showed that maximal diameter of the shunts ( P  = 0.012) and serum Mac‐2 binding protein glycosylation isomer levels at the end of treatment ( P  = 0.005) were associated with the development of portal hypertension‐related events, with cut‐off values of 5.25 mm ( P  = 0.001) and 6.84 cut‐off index ( P  < 0.001), respectively. The increase of serum albumin levels at 3 years, as compared with the baseline, was smaller in 22 patients having shunts with maximal diameters of ≥5 mm than in the remaining 57 patients ( P  = 0.034), whereas no such difference was seen between the patients with and without elevation of serum Mac‐2 binding protein glycosylation isomer level of ≥6.8 cut‐off index. Conclusions: A large size of portosystemic shunts was found to be a crucial determinant of impaired improvement of liver function, as well as of the development of portal hypertension‐related events, even after sustained viral response in patients with compensated cirrhosis.